Penerapan Mobilisasi Dini Pada Pasien Post Operasi Sectio Caesar Di Ruang Nifas Rumah Sakit Dr R Soeharsono Banjarmasin - Jamilah, Sri; Sri Purwanti Ariani; Putri Lestari (CV. ITTC INDONESIA, 2024)
A common issue experienced by post-cesarean section patients is impaired physical mobility. Early mobilization post-cesarean section is conducted to prevent immobilization complications. This study aims to implement early mobilization in post-cesarean section patients. The research design utilizes a descriptive method in the form of a case study with a nursing process approach. Nursing care was provided to two post-cesarean section patients with physical mobility issues. This case study explores nursing care in post-cesarean section patients experiencing impaired physical mobility through teaching early mobilization and providing health education on early mobilization. The inclusion criteria were 4-6 hours post-cesarean section with spinal anesthesia, and the exclusion criteria were post-cesarean section primigravida patients. The research results indicate that the implementation of early mobilization nursing care can reduce mobility problems, as both patients were able to walk and engage in activities independently. The provision of early mobilization nursing interventions effectively influences the resolution of physical mobility impairments experienced by patients, enabling them to perform activities as usual and increase their knowledge about early mobilization post-cesarean section.